The Routledge history of the Devil in the Western tradition
1 online resource.
Keywords: "Covering a period of two thousand years, this book offers an interdisciplinary exploration of the devil's role in the Western tradition and draws from history, religion, art, literature, media studies and anthropology to provide a multifaceted view of the devil over time. The Routledge History of the Devil in the Western Tradition examines topics such as the devil's scriptural origins, medieval development, and role in witch-hunting and possession cases, as well as the influence of the demonic on contemporary issues like terrorism, political polarisation, and digital culture. Collectively, this volume demonstrates that the demonological imagination has served as part of the glue holding western societies together. While contexts, misfortunes and anxieties have shifted according to time and place, many of the dynamics that underlie the devil's construction and detection have important continuities. This book, then, provides an innovative history of the anti-west-the west as seen through its anxieties, fears, and attempts to define and police itself and its boundaries. With contributions from 28 leading scholars in the field, this volume is of interest to all students and scholars of the devil in the Western world"--